Microstructure, defect structure and hydrogen trapping in zirconium alloy Zr-1Nb treated by plasma immersion Ti ion implantation and deposition - Kashkarov E. B. Egor Borisovich; Nikitenkov N. N. Nikolai Nikolaevich; Sutygina A. N. Alina Nikolaevna; Laptev R. S. Roman Sergeevich; Bordulev Yu. S. Yuri Sergeevich; Obrosov A. Aleksey; Liedke Mac Iej Oskar; Wagner A. Andreas; Zak A. Andrzej; Weifs S. Sabine (2018, 2018)
Title screen